Tinjauan Fikih Munakahat Madzab Imam Syafi’i terhadap Istri yang Tidak Patuh kepada Suami Dikarenakan Tidak Memberi Nafkah - Yayat Hidayat; Ahmad Mubasir (El 'Ailaah, 2023)
In Islam, giving maintenance is the husband's obligation, while being obedient and obedient is the wife's obligation. If the husband does not carry out his obligations, problems will arise such as a wife who is disobedient to her husband. This study aims to find out : How husbands should support their wives according to the Syafi'i Madzab, How should the wife's obedience to her husband according to the Syafi'i Madzab, How is the review of Islamic law towards a wife who is disobedient to her husband because not supported according to the Shafi'i Madzab. This study used a qualitative research method with a type of library research (Library Research). The data collection technique used is a documentation study. Based on the data that has been studied in the book of the Syafi'i Madzab, it is concluded that it is obligatory for the husband to give a living to his wife in the form of material and non-material (inner) income. The level of maintenance is two mud for rich husbands, one mud for poor husbands, and one and a half mud for middle husbands every day. Then provide shelter, clothing and servants to the wife if they are usually served. In addition, it is obligatory for the husband to have intercourse with his wife with ma'ruf. The wife is obliged to carry out all the husband's orders as long as they do not contain disobedience, because the obedience and obedience of a wife to her husband is obligatory. If a husband does not carry out his obligations in providing a living to his wife, then the wife is given two choices, namely to be patient and remain with her husband under these circumstances, or to enter into a marriage. And disobeying your husband because you don't get a living is permissible.